The just war myth the moral illusions of war - Fiala, Andrew G. (Andrew Gordon), 1966- (Lanham : Rowman & Littlefield Publishers, 2007)
As war continues to be a primary topic in public debate, Andrew Fiala in The Just War Myth critically examines the concept of just war, arguing that actual wars never live up to the ideals of just war theory. The book provides a historical overview of the just war idea and also turns a critical eye on current events, including the idea of preemptive war, the use of torture, and the unreality of the Bush Doctrine.
Title Page; Copyright Page; Contents; Preface; PART I: THE JUST WAR MYTH; 1 Introduction: The Just War Myth and the Politics of War; 2 The Myths and Memes of Political Life; 3 Genealogy of the Just War Tradition; 4 Duels and Modern Wars; 5 The Myth of American Exceptionalism; PART II: THE MYTHS OF THE WAR ON TERRORISM; 6 The Preemptive War Doctrine; 7 Torture and Terrorism; 8 Humanitarian Intervention and the Crusade for Democracy; 9 Jus in Bello and the War in Iraq; PART III: SKEPTICAL DEMOCRATIC PACIFISM; 10 The Myth of Pacifism; 11 Citizenship, Responsibility, and Peace; Works Cited; Index
Description based upon print version of record.
About the Author
Keywords: Just war doctrine; Just war doctrine; POLITICAL SCIENCE / General; Electronic books